Quality improvement in maternal and newborn healthcare: lessons from programmes supported by the German development organisation in Africa and Asia. Issue 5 (6th September 2019) - Goyet, Sophie; Broch-Alvarez, Valerie; Becker, Cornelia
Abstract : Improving the quality of maternal and child healthcare (MCH) is a mandatory step on the path to reaching the Sustainable Development Goals and Universal Health Coverage. Quality improvement (QI) in MCH is a strong focus of the bilateral development cooperation provided by Germany to help strengthen the health systems of countries with high maternal and child mortality rates and/or with high unmet needs for family planning. In this article, we report on the findings of an analysis commissioned by a community of practice on MCH, of Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). The objectives were to review the QI interventions implemented through programmes which have received technical assistance from GIZ on behalf of the German Federal Ministry for Economic Cooperation and Development in 14 Asian and African countries, to identify and describe the existing approaches and their results, and finally to draw lessons learnt from their implementation. Our analysis of the information contained in programme documents and reports identified five main methodologies used to improve the quality of care: capacity-building and supervision, governance and regulation, systemic QI at facility level, support to infrastructures, and community support. It is difficult to attribute the observed progresses in maternal and neonatal health to a particular agency, programme or intervention. We acknowledge that systemic implementation research embedded within the programmes would facilitate an understanding of the determinants of successful QI interventions, would better assess their effectiveness, and therefore better guide future bilateral aid programmatic decisions.